ANALISIS PENGARUH HIDROLIKA SUNGAI TERHADAP TRANSPORT BOD DAN DO DENGAN MENGGUNAKAN SOFTWARE QUAL2E (STUDI KASUS DI SUNGAI KALIGARANG, SEMARANG ) - Nugraha, Winardi Dwi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
People and industrial activity along Kaligarang River increase day by day, cause load of riverÂ increase too. River has many function to support human life, so monitoring of river is neededÂ Monitoring Â of Â river Â water quality Â in Â some Â places Â need Â many Â expenses Â and Â can Â not Â giveÂ information Â abaout Â water Â quality comprehensively. Â That Â is Â why, Â itâ€™s Â needed Â a Â water Â qualityÂ modeling for river. In this case, itâ€™s used Qual2E one of the water quality modeling software. ToÂ use the software related to the river characteristic, itâ€™s still needed to justify some of coefficients Â Â and Â get Â validation Â related Â to Â reaction Â pattern Â among the Â constituent, Â hydraulic Â condition, Â andÂ hidrology aspects. The research is proposed to see the process of calibration of model relatedÂ to the justification of coefficient.And so, to analyze the influence of hydraulic aspects of river toÂ the BOD and DO pattern. Itâ€™s needed the secondary data, i.e. water quality sampling, climatlogy,Â hydrology (discarge of river), river hydraulic aspects, map, point source.The calibration is doneÂ related to the data and coefficient of the model to get the suitable model used Kaligarang River.Â This Â calibrated Â model Â is Â validated Â by Â the Â secondary Â data, Â i.e. Â water Â quality sampling Â fromÂ Bappedal Province of Central Java. And the get simulation with the various of hydraulic aspects,Â i.e. â€œnâ€ number of Manning, cross section, and the influence of Simongan dam. The conclusionsÂ of the research say that there are influences and relationships of hydraulic aspects to the BODÂ and DO pattern.